The fall, recovery, classification, and initial characterization of the Hamburg, Michigan H4 chondrite. (27th October 2020) - Heck, Philipp R.; Greer, Jennika; Boesenberg, Joseph S.; Bouvier, Audrey; Caffee, Marc W.; Cassata, William S.; Corrigan, Catherine; Davis, Andrew M.; Davis, Donald W.; Fries, Marc; Hankey, Mike; Jenniskens, Peter; et al.
Abstract: The Hamburg meteorite fell on January 16, 2018, near Hamburg, Michigan, after a fireball event widely observed in the U.S. Midwest and in Ontario, Canada. Several fragments fell onto frozen surfaces of lakes and, thanks to weather radar data, were recovered days after the fall. The studied rock fragments show no or little signs of terrestrial weathering. Here, we present the initial results from an international consortium study to describe the fall, characterize the meteorite, and probe the collision history of Hamburg. About 1 kg of recovered meteorites was initially reported. Petrology, mineral chemistry, trace element and organic chemistry, and O and Cr isotopic compositions are characteristic of H4 chondrites. Cosmic ray exposure ages based on cosmogenic 3 He, 21 Ne, and 38 Ar are ~12 Ma, and roughly agree with each other. Noble gas data as well as the cosmogenic 10 Be concentration point to a small 40–60 cm diameter meteoroid. An 40 Ar‐ 39 Ar age of 4532 ± 24 Ma indicates no major impact event occurring later in its evolutionary history, consistent with data of other H4 chondrites. Microanalyses of phosphates with LA‐ICPMS give an average Pb‐Pb age of 4549 ± 36 Ma. This is in good agreement with the average SIMS Pb‐Pb phosphate age of 4535.3 ± 9.5 Ma and U‐Pb Concordia age of 4535 ± 10 Ma. The weighted average age of 4541.6 ± 9.5 Ma reflects the metamorphic phosphate crystallization age after parent body formation in the early solar system.